(untitled) (Revista Música, 1995)
A composer whose first works date from his early thirties and whose first important, large-scale composition does not appear until the age of thirty-seven could well be perceived as a late starter. This to some extent was the case with Maurice Ohana. The earliest works which he allowed to remain in his catalogue were composed towards the end of the Second World War when, taking advantage of his army posting to Italy, he enrolled in the piano class of Alfredo Casella at the Academia Santa Cecilia in Rome. Although he established his compositional presence later than most others belonging to that illustrious generation of composers born in and around 1913, it would be misleading to suggest that Ohana either came to music late in life or was to any extent a late developer. His real beginnings as a composer were delayed not only by the Second World War, but by the success of his first career as a concert pianist which he pursued throughout the 1930s and for some time after his war service. It is not surprising, therefore, that music for his own instrument, the piano, should figure prominently in Ohanas catalogue. Indeed, much of his compositional development is reflected through his work in this medium, his music for solo piano spanning almost all of his creative years from the mid 1940s to the mid 1980s.